1984
DOI: 10.1093/geronj/39.6.648
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Endocrine Time Structure in Humans Above 80 Years of Age

Abstract: The circadian rhythms in blood hormone concentrations of 17 pituitary, adrenal, pancreatic, testicular, and thyroid hormones were determined in 9 women and 5 men 81 to 91 years of age. Six samples over a 24-hr span were studied for each hormone. Even with the small sample available, 9 of the 17 hormones determined showed a statistically significant circadian rhythm as a group phenomenon (prolactin, estradiol, 17-hydroxyprogesterone, insulin, C-peptide, thyroid stimulating hormone, aldosterone, cortisol, dehydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The phase delay of the circadian cortisol secretion found in elderly men, as compared to young adults, agrees with some previous reports [12,19). Based on a similar sam pling at 4-hour intervals, however, Touitou et al [22] and Lakatua et al [10] did not find any phase difference in cortisol secretion between elderly and young subjects. Sherman et al [20] recently demonstrated an age-related phase advance in cortisol circadian rhythm, suggesting that this might be the consequence of a different sleepwake schedule in elderly or.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The phase delay of the circadian cortisol secretion found in elderly men, as compared to young adults, agrees with some previous reports [12,19). Based on a similar sam pling at 4-hour intervals, however, Touitou et al [22] and Lakatua et al [10] did not find any phase difference in cortisol secretion between elderly and young subjects. Sherman et al [20] recently demonstrated an age-related phase advance in cortisol circadian rhythm, suggesting that this might be the consequence of a different sleepwake schedule in elderly or.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in accordance with a pre vious report by Kahn-Dawood et al [9], who demon strated that young adults have significantly higher plasma fT levels in the morning than in the evening, by means of an equilibrium dialysis method. The circadian variations of the unbound T fraction are probably a stoi chiometric consequence of the T and binding proteins circadian rhythms [4,16], since the relative distribution of a steroid hormone between the protein bound and the free fraction strongly depends upon the actual plasma concentrations of both steroid and protein [6], In elderly men the frequent loss of T circadian rhythm is an aspect of an age-related impairment of the pituitary-gonadal function, as we [11] and others [3,10] have previously reported. Unexpectedly, in spite of the lack of total T rhythmic circadian variation, our old subjects showed a clear fT rhythm which was of smaller amplitude and very advanced in phase and with very wide confidence limits when compared to that of young subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies in humans suggest that basal cortisol levels do not change with age (West et al, 196 1;Friedman et al, 1969;Jensen and Blichert-Toft, 197 1;Weitzman et al, 197 1;Zumoff et al, 1974;Colucci et al, 1975;Lakatua et al, 1984;Linkowski et al, 1985;Sherman et al, 1985;Pavlov et al, 1986;Jensen et al, 1988;Sharma et al, 1989;Waltman et al, 1991). However, as in the Long-Evans rat, neuropathology in aged humans is associated with increased basal glucocorticoid levels (Davis et al, 1986;DeLeon et al, 1988;Dodt et al, 1991).…”
Section: Basal Cortisol Levels and Cognitive Deficits In Human Agingmentioning
confidence: 99%
“…There are numerous studies, utilizing various tests, that suggest an impaired glucocorticoid feedback regulation in aged humans (O'Brien et al, 1994;Seeman and Robbins, 1994;Born et al, 1995). However, reports about ageassociated changes in the basal activity of the HPA axis in humans are ambiguous: some found the cortisol levels in young and elderly individuals to be similar (Lakatua et al, 1984;Waltman et al, 1991;Born et al, 1995;Gotthardt et al, 1995), others observed ageassociated increases in basal plasma cortisol concentrations (Halbreich et al, 1984;Pfohl et al, 1985) while yet others even observed decreased basal cortisol plasma concentrations with aging (Drafta et al, 1982;Sherman et al, 1985;Maes et al, 1994).…”
Section: Introductionmentioning
confidence: 99%